Survival of Black and White Patients With Stage IV Small Cell Lung Cancer - Shi, Huashan; Zhou, Kexun; Cochuyt, Jordan; Hodge, David; Qin, Hong; Manochakian, Rami; Zhao, Yujie; Ailawadhi, Sikander; Adjei, Alex A.; Lou, Yanyan (Frontiers in Oncology, 2021)
Background Small cell lung cancer (SCLC) is associated with aggressive biology and limited treatment options, making this disease a historical challenge. The influence of race and socioeconomic status on the survival of stage IV SCLC remains mostly unknown. Our study is designed to investigate the clinical survival outcomes in Black and White patients with stage IV SCLC and study the demographic, socioeconomic, clinical features, and treatment patterns of the disease and their impact on survival in Blacks and Whites. Methods and Results Stage IV SCLC cases from the National Cancer Database (NCDB) diagnosed between 2004 and 2014 were obtained. The follow-up end point defined as death or the date of last contact. Patients were divided into 2 groups by white and black. Features including demographic, socioeconomic, clinical, treatments and survival outcomes in Blacks and Whites were collected. Mortality hazard ratios of Blacks and Whites stage IV SCLC patients were analyzed. Survival of stage IV SCLC Black and White patients was also analyzed. Adjusted hazard ratios were analyzed by cox proportional hazards regression models. Patients’ median follow-up time was 8.18 (2.37-15.84) months. Overall survival at 6, 12, 18 and 24 months were 52.4%, 25.7%, 13.2% and 7.9% in Blacks in compared to 51.0%, 23.6%, 11.5% and 6.9% in Whites. White patients had significantly higher socioeconomic status than Black patients. By contrast, Blacks were found associated with younger age at diagnosis, a significantly higher chance of receiving radiation therapy and treatments at an academic/research program. Compared to Whites, Blacks had a 9% decreased risk of death. Conclusion Our study demonstrated that Blacks have significant socioeconomic disadvantages compared to Whites. However, despite these unfavorable factors, survival for Blacks was significantly improved compared to Whites after covariable adjustment. This may be due to Blacks with Stage IV SCLC having a higher chance of receiving radiation therapy and treatments at an academic/research program. Identifying and removing the barriers to obtain treatments at academic/research programs or improving the management in non-academic centers could improve the overall survival of stage IV SCLC.